FOOD PREFERENCE OF GERMAN COCKROACH Blatella germanica FOR TYPES OF SUGAR MOLECULE - Ihsan Fathurrahman , Muhammad
Food preference of animals is influenced by internal factors (e.g. anatomy, physiology, gender, age) and external factors (environment and origin). Knowledge of animal feeding behavior can help people to deal with the problems caused by animals that become pests for humans. German cockroach (Blatella germanica) is one of the pests that often interfere with comfort so that people are always looking for means to overcome them. One of method is using a pellet-shaped bait containing attractant to eradicate pests. The most commonly used attractant usually have a sugar content. This study aims to determine the food preference of German cockroaches to monosaccharide (fructose and glucose) and disaccharide (sucrose and maltose) sugar molecule by sex (male and female) and strain (origin) of German cockroaches. The behavioral test of preference was performed within the test area (25cm x 50cm x 30cm) containing 3 individuals of the same sex in the same strain exposed to 5 stimuli (4 sugars + 1 control), and 1 shelter for 12 hours. Observations were performed by behavior sampling through CCTV recordings that were analyzed using data playback recording. The parameters measured are how fast the individual cockroaches go to the stimulus (latency) and how often the individual cockroach is in one of these stimuli (frequency). Tests were performed on male and female adult cockroaches of three strains of German cockroaches encountered in Indonesia (Kalimantan strain, Sulawesi strain, and Surabaya strain). The test results showed a significant difference by the cockroach in choosing a sugar stimulus (p <0.01) and generally showed that German cockroach prefer the type of sucrose sugar compared to other types of sugar. There were also significant differences between each cockroach strain in selecting a sugar stimulus (p <0.05) with more Kalimantan strain move toward the stimulus more than the other strains. Also known for male and female gender are almost significantly different in frequency to the stimulus. For latency, it is known that Sulawesi strains move faster towards the stimulus although statistical test results do not show any significant difference for all categories (strains, gender, and stimuli). It can be concluded that German cockroaches prefer sucrose than other sugars and have a noticeable difference in sugar preferences and have a noticeable difference for German cockroach strains to the stimulus, and show that gustatory receptor functions work more effectively than olfactory receptor in the search for stimuli.